Synthesis and in vitro biological evaluation of novel diaminothiophene scaffolds as antitumor and anti-influenza virus agents. Part 2. Issue 50 (19th June 2017) - Bozorov, Khurshed; Zhao, Jiang yu; Nie, Li Fei; Ma, Hai-Rong; Bobakulov, Khayrulla; Hu, Rui; Rustamova, Nigora; Huang, Guozheng; Efferth, Thomas; Aisa, Haji A.
Abstract : Herein, we report the synthesis and biological evaluation of a novel series of diethyl 2, 5-diaminothiophene-3, 4-dicarboxylate (DDTD) derivatives as antitumor and anti-influenza virus agents. Abstract : On the basis of high-throughput screening, fragment-based drug discovery, structure–activity relationships and building block analysis methods, herein we report the synthesis and biological evaluation of a novel series of diethyl 2, 5-diaminothiophene-3, 4-dicarboxylate derivatives. All of the prepared Schiff bases (with mono-, di- and poly-substituents at the aromatic portion), mono- and bis-amides of diethyl 2, 5-diaminothiophene-3, 4-dicarboxylate, were evaluated against various human cancer and non-cancerous (only for active compounds) cell lines, as well as influenza A (subtypes FM/1/47/H1N1, hanfang/359/95/H3N2) and B (subtype jifang/13/97) viruses. The obtained results suggest that some selected compounds revealed promising antitumor and antiviral activities and may serve as lead compounds for further drug discovery and development.